ANALYSIS OF THE SOCIAL MEDIA USE, SERVICE QUALITY, AND AVAILABILITY OF FACILITIES TO THE INTEREST OF TOURIST VISITING KEBON EMPIRING SRIMULYO TOURISM - Wisnu Hadi; Lina Ayu Safitri; Chriswardana Bayu Dewa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Tourism can have multiple effects on all sectors such as economic, social, cultural and political so that it becomes the target of national and regional development. One of the tourism objects to be developed is the nature tourism of Kebon Empring, Srimulyo, Bantul. As an effort to develop this area, researchers want to analyze the effect of social media promotion, available facilities and service quality on tourist visits at Kebon Empring tourism objects, Srimulyo, Bantul. The method used in this research uses quantitative research where research data is obtained from primary data sources in the form of questionnaire data collection. In this study the independent variable (X) consisted of the use of social media, quality of service and availability of facilities, while the dependent variable (Y) was interest in visiting. The results of this study provide several conclusions that the variable hypothesis of social media use is rejected. Meanwhile, the variables of service quality and availability of facilities have a significant effect on interest in visiting.